Role of reduced glutathione in improving post-thaw seminal parameters in poor freezable Jersey crossbred bull semen - Ponraj, Perumal; Selvaraju, S; Barik, A K; Mohanty, D N; Das, S; Mishra, P C (The Indian Journal of Animal Sciences, 2011)
The role of reduced glutathione in improving the post thaw seminal characters in good and poor freezable Jersey crossbred bull semen was studied and compared with the control group. Two test groups, the test group each contains 18 ejaculates in both good and poor freezable bull. The reduced glutathione was added (5mM) to the conventional Tris extender, fast freezing and followed by thawing and measured the post thaw seminal parameters. Out these parameters the total motility has showed significant (p < 0.05) different between the two groups in both freezable bull semen, where as the other parameters such as livability, total sperm abnormality, loss of acrosomal integrity, percentage of hypo osmotic swelling positive sperm and vanguard distance traveled by sperm (mm/hour) in cervical mucus were highly significant (p < 0.01) between the reduced glutathione treated and control group. However, the lipid peroxide formation is none-significant between the two groups, but the glutathione had reduced the production of more ROS as compared to the control group. The addition of reduced glutathione had maintained the functional parameters of good and enhances the poor freezable semen. Thus the reduced glutathione improves post thaw sperm functional parameters such as motility, viability, functional membrane integrity and acrosomal integrity in poor freezable semen suggesting that addition of glutathione in semen extender may improve fertility in these bulls.